2015
DOI: 10.1007/s10067-015-3131-7
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of interventions to improve knowledge and self-management skills concerning contraception, pregnancy and breastfeeding in people with rheumatoid arthritis

Abstract: This systematic review aimed to determine the effectiveness of interventions for improving knowledge and/or self-management skills concerning contraception, pregnancy and breastfeeding in people with rheumatoid arthritis (RA). We searched four databases (MEDLINE, CINAHL, Cochrane Trials, PsycINFO) using a comprehensive search strategy. Studies were eligible if they were prospective, published in English from 2004 to 2015, included participants with RA and tested an intervention designed to improve knowledge an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 44 publications
1
15
0
1
Order By: Relevance
“…Although we did not include patients in our sample, the foci for the Delphi were directly informed by previous empirical, consumer-based research, consistent with the approach adopted by Hawker et al 30. The results from this study and our recent systematic review11 point to the opportunity to develop and evaluate targeted educational interventions for this group of consumers.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Although we did not include patients in our sample, the foci for the Delphi were directly informed by previous empirical, consumer-based research, consistent with the approach adopted by Hawker et al 30. The results from this study and our recent systematic review11 point to the opportunity to develop and evaluate targeted educational interventions for this group of consumers.…”
Section: Discussionmentioning
confidence: 96%
“…In particular, our data suggest that women with RA have clear pregnancy-related educational needs and seek specific information from their care providers about medicines safety during pregnancy and breast feeding, physical and emotional support services and practical coping strategies to manage pain and flares during the postnatal period 6. Moreover, in a recent systematic review and editorial, we identified a lack of self-management interventions for women with RA targeted towards these issues,9 11 despite European League Against Rheumatism (EULAR) recommendations that specific patient education is critical at important life and disease course stages12 and published Standards of Care for RA that recommend comprehensive and individually tailored education about RA and its management 13. While some consumer texts14 15 and arthritis organisation web pages have been developed to address information gaps in this area, they remain limited and inadequately address some of the most important issues raised by women relating to disease management and medicines safety during pregnancy and breast feeding 5…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Women with ARDs encounter a range of challenges when they begin to approach a transitional journey during their childbearing years, including fertility, timing pregnancies, increased risk of miscarriage, changes in disease activity, risks and benefits of medication and treatment during pregnancy and breastfeeding, and managing pain and physical limitations when caring for young children (Nightingale et al, 2006;Ostensen & Ceti, 2015;Signore et al, 2011). Research has highlighted the lack of information available to women during this emotive and challenging time, and more integrated care has been recommended (Ackerman et al, 2016;.…”
Section: Background To the Star Family Studymentioning
confidence: 99%
“…Self-management education programs highlight the role of patient education in protective and therapeutical health-care activities and consist of organized learning experiences usually designed to facilitate the adoption of health-promoting behaviors. Self-management interventions often involve various skills regarding the disease, including problem solving, decision-making, and relations with health professionals [99,100]. Self-management interventions are person-centered, and they focus on encouraging active participation of the individuals in order for them to develop their well-being and to manage the symptoms [101].…”
Section: Self-managementmentioning
confidence: 99%